PENENTUAN POTENSI GEMPA BUMI MERUSAK BERDASARKAN PARAMETER KEGEMPAAN DI WILAYAH BUSUR BANDA - Drajat Ngadmanto (Widyariset, 2010)
Banda arc has a high seismicity, therefore, it is necessary to reduce the earthquake risk. Earthquake parameters variation from Gutenberg - Richter relation, log n(M)=a – bM, has introduced the model of earthquakes prediction related to earthquake risk. Earthquake data from NEIC catalogue for a period of 1973 - 2009 has been used to analyze earthquake parameters variation (a-value, b-value) in the area of Banda arc within coordinates 1°-13° S and 120°-135° E. This research used ZMAP ver. 6.0. to analyze the earthquake data. The result of spatial analyze shows the areas of potential destructive earthquakes are surrounding of Flores, Alor and western part of Seram. The probability of earthquakes occurrence with the magnitude 6.5 RS in these areas is 7 – 15 years, whereas the magnitude 7 RS is about 20–60 years.